In vivo assay and modelling of protein and mitochondrial turnover during aging. Issue 1 (2nd January 2021) - S. Bell, Hans; Tower, John
ABSTRACT: To maintain homoeostasis, cells must degrade damaged or misfolded proteins and synthesize functional replacements. Maintaining a balance between these processes, known as protein turnover, is necessary for stress response and cellular adaptation to a changing environment. Damaged mitochondria must also be removed and replaced. Changes in protein and mitochondrial turnover are associated with aging and neurodegenerative disease, making it important to understand how these processes occur and are regulated in cells. To achieve this, reliable assays of turnover must be developed. Several methods exist, including pulse-labelling with radioactive or stable isotopes and strategies making use of fluorescent proteins, each with their own advantages and limitations. Both cell culture and live animals have been used for these studies, in systems ranging from yeast to mammals. In vivo assays are especially useful for connecting turnover to aging and disease. With its short life cycle, suitability for fluorescent imaging, and availability of genetic tools, Drosophila melanogaster is particularly well suited for this kind of analysis.